73‐2: Invited Paper: Active Switching LCP‐based Microlens Arrays for 3D Display and Imaging Applications. Issue 1 (May 2017) - Park, Min-Kyu; Joo, Kyung-Il; Park, Heewon; Jeong, Hee-Dong; Kim, Hak-Rin
Abstract : We demonstrate a well‐aligned polarization‐dependent reactive mesogen (RM) microlens array with small f‐number and small pitches by using a top‐down alignment method. By using the polarization dependent RM lens array with the small f‐number, the small pitch, and the fast switching property, we realized a 2D/3D switchable portable three‐dimensional (3D) display and imaging system with 2D/3D switching function. In addition, the 3D viewing parameter such as 3D image resolution, viewing resolution were improved by utilizing a time‐multiplexing method with specially designed polarization‐dependent RM microlens arrays.